2022
DOI: 10.3390/foods11203183
|View full text |Cite
|
Sign up to set email alerts
|

Phycocyanin Protects against High Glucose High Fat Diet Induced Diabetes in Mice and Participates in AKT and AMPK Signaling

Abstract: Phycocyanin is a type of marine natural product and functional food additive. Studies have demonstrated that phycocyanin has potential regulatory effects on glycometabolism, while its function and mechanism, especially in type 2 diabetes mellitus (T2DM), is still unclear. The aim of this study was to investigate the antidiabetic roles and underlying mechanism of phycocyanin in a high glucose high fat diet induced model of T2MD in C57BL/6N mice and a high-insulin-induced insulin-resistant model of SMMC-7721 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Thereafter, the positive effects of C-PC in the treatment of diabetes were confirmed by a further study conducted on both cellular and animal models [ 71 ]. It was observed that specifically in mice with type 2 diabetes mellitus (T2DM) that were treated orally with 200 mg kg −1 and in insulin-resistant cells, C-PC increased insulin sensitivity and the cellular use of glucose through the activation of AMP-activated protein kinase (AMPK), which, once active, promotes autophagy, and of serine/threonine kinase 1 (AKT), which is part of the phosphatidylinositol-3 kinase (PI3K) pathway and is relevant in the regulation of the glyco-metabolism [ 71 ].…”
Section: Health Promoting Effectsmentioning
confidence: 93%
See 1 more Smart Citation
“…Thereafter, the positive effects of C-PC in the treatment of diabetes were confirmed by a further study conducted on both cellular and animal models [ 71 ]. It was observed that specifically in mice with type 2 diabetes mellitus (T2DM) that were treated orally with 200 mg kg −1 and in insulin-resistant cells, C-PC increased insulin sensitivity and the cellular use of glucose through the activation of AMP-activated protein kinase (AMPK), which, once active, promotes autophagy, and of serine/threonine kinase 1 (AKT), which is part of the phosphatidylinositol-3 kinase (PI3K) pathway and is relevant in the regulation of the glyco-metabolism [ 71 ].…”
Section: Health Promoting Effectsmentioning
confidence: 93%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/nu16111752/s1, Table S1: Effects of C-PC or PCB-B on different disease models [20,[24][25][26][27][28][29][30][31][32][33][34]36,[38][39][40][41][43][44][45][46][47][48][49][50][51][52][62][63][64][65][66][67][68]71,72,[76][77][78][79][80][81][82][85][86][87][88][90][91][92]...…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…This induces glycation and leads to the formation of macromolecules that accumulate in the heart, blood vessels, eyes, and kidneys [27,89]. Some studies have demonstrated that phycocyanin is an antidiabetic agent and has an antiglycation activity that reduces the side effects of diabetes [89][90][91][92]128]. Phycocyanin promoted glucose uptake in an insulin-resistant cell line [77] and inhibited αamylase and β-glucosidase in vitro, attenuating starch absorption [88,129,130].…”
Section: Anti-oxidativementioning
confidence: 99%
“…AMPK is a key regulator of energy metabolism and glucose homeostasis. Several algae-derived compounds, such as fucoidan from the brown macroalga F. vesiculosus [ 120 ] and phycocyanin from the blue-green microalga Arthrospira platensis [ 121 ], have been found to activate AMPK. The activation of AMPK leads to increased glucose uptake, enhanced insulin sensitivity, and improved glycemic control.…”
Section: Mechanistic Insights and Molecular Targetsmentioning
confidence: 99%